1994
DOI: 10.4310/mrl.1994.v1.n6.a14
|View full text |Cite
|
Sign up to set email alerts
|

The Genus of Embedded Surfaces in the Projective Plane

Abstract: A b s t r a c t . We show how the new invariants of 4-manifolds resulting from the Seiberg-Witten monopole equation lead quickly to a proof of the 'Thom conjecture'. Statement of the resultThe genus of a smooth algebraic curve of degree d in CP 2 is given by the formula g = (d − 1)(d − 2)/2. A conjecture sometimes attributed to Thom states that the genus of the algebraic curve is a lower bound for the genus of any smooth 2-manifold representing the same homology class. The conjecture has previously been proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
387
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(395 citation statements)
references
References 14 publications
4
387
0
4
Order By: Relevance
“…In §2.1, we review the construction of the moduli spaces of PU(2) monopoles M t from [24], but now phrased in the convenient and more compact framework of "spin u structures" t. In §2.2 we recall our Uhlenbeck compactness and transversality results for the moduli spaces of PU(2) monopoles from [24] and [15]. In §2.3, we recall the construction of the moduli space of Seiberg-Witten monopoles M s as in [43], [45], [56], but with non-standard perturbations so we can directly identify these moduli spaces with strata of reducible PU(2) monopoles. Our transversality result [15] ensures that the natural stratification of the Uhlenbeck-compactified moduli space of PU (2) monopoles is smooth.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…In §2.1, we review the construction of the moduli spaces of PU(2) monopoles M t from [24], but now phrased in the convenient and more compact framework of "spin u structures" t. In §2.2 we recall our Uhlenbeck compactness and transversality results for the moduli spaces of PU(2) monopoles from [24] and [15]. In §2.3, we recall the construction of the moduli space of Seiberg-Witten monopoles M s as in [43], [45], [56], but with non-standard perturbations so we can directly identify these moduli spaces with strata of reducible PU(2) monopoles. Our transversality result [15] ensures that the natural stratification of the Uhlenbeck-compactified moduli space of PU (2) monopoles is smooth.…”
Section: 3mentioning
confidence: 99%
“…We note that in the usual presentation of the Seiberg-Witten equations [43], [60], one takes τ = id Λ + and ϑ = 0, while η is a generic perturbation. However, we shall see in Lemma 3.12 that in order to identify solutions to the Seiberg-Witten equations (2.55) with reducible solutions to the PU(2) monopole equations (2.32), we need to employ the perturbations given in equation (2.55) and choose…”
Section: Moduli Spaces Of Seiberg-witten Monopolesmentioning
confidence: 99%
“…We sum up the basic properties of the Seiberg-Witten invariants, which have been developed by many people: see for example [KM,Tl,T2] and [W]. (K x ) = ±1.…”
Section: Review Of Seiberg-witten Invariantmentioning
confidence: 99%
“…The Seiberg-Witten equations [1] do not admit nonsingular solutions unless the curvature of the four dimensional base manifold M happens to be negative over some regions of M. In particular,if M = R 4 , the Weitzenbock formula implies that the modulus squared of the spinor field ψ must either vanish everywhere, or exhibit singularities instead of local maxima [2]. There is also a global restriction on flat-space Seiberg-Witten solutions: Integrating the Weitzenbock formula, Witten [1] showed that all nontrivial flat solutions, including dimensionally reduced ones based on R 3 , R 2 or R 1 , are all necessarily non-L 2 .…”
mentioning
confidence: 99%